Normotensive HELLP syndrome in the midst of Dengue fever - Manappallil, Robin George; Surendran, Sithara; Kumar, Anoop; Prasad, Ganga (Asian Journal of Medical Sciences, 2018)
HELLP syndrome is a life threatening complication of pregnancy, characterized by haemolysis, elevated liver enzymes and low platelet counts. Preeclampsia is a risk factor for developing HELLP. However, some patients can have HELLP in the absence of elevated blood pressure. Dengue fever is a mosquito-borne viral infection characterized by fever, leucopenia and thrombocytopenia, and bleeding manifestations. This is a case of a young primigravida who presented with dengue fever and was found to have an associated normotensive HELLP syndrome. Asian Journal of Medical Sciences Vol.9(2) 2018 40-42